(untitled) (Web of Teachers: Inderscience Research, 2024)
This article explores the associative field of the Famille-Oila concept through a comparative linguistic and cultural study of French and Uzbek linguistic cultures. Drawing on the framework of anthropocentric linguistics, the research investigates how the family concept is cognitively and culturally perceived in these distinct contexts. The study employs free associative experiments conducted among students in France and Uzbekistan, analyzing responses to stimuli related to the roles of "family," "father," and "mother." The findings reveal both universal and culture-specific associations, highlighting the influence of cultural, social, and psychological factors on linguistic cognition. Despite differences, the study underscores the universal significance of the family as a fundamental societal value across cultures.